Percutaneous cannulation of central veins in neonates: Its safety and feasibility: Audit of 75 neonatal insertions - Jadhav, Vinay; Shankar, Gowri; Deepak, J; Babu, Narendra (Indian Journal of Child Health, 2016)
Introduction: Central venous catheters (CVC) have become an integral part in the care of children in intensive care settings. However, their use in neonates is limited due to inherent difficulties in insertion and associated complications. Objective: We present our experience in the use of CVC by percutaneous cannulation in neonates. Materials and Methods: A total of 75 cases of neonatal percutaneous central venous cannulation inserted over a period of 6-month from March 2014 to August 2014. Data regarding age, indication for central line insertion, site of insertion, complications related to central line insertion, duration of catheter days, werecollected. Results: Of the 75 neonates, 49 were male and 26 were female. Age group ranged from 14 to 30 days with a median of 21 days. Weight ranged from 750 g to 3.5 kg with an average of 1.9 kg. The internal jugular vein was accessed in 45 (60%), followed by femoral 26 (34.6%) and subclavian in 4 (5.3%) cases. Successful percutaneous cannulation was achieved in all and the median catheter days were 12 days. The longest catheter patency was 46 days in one neonate. The most common indication for placement was failure of peripheral venous access (78%). The main complications encountered were catheter displacement (12%) and catheter malposition (9.3%). Catheter induced sepsis was seen in 7 (9.3%) neonates. Conclusion: Percutaneous cannulation of central veins in neonates is feasible, and safe, with acceptable morbidity. Ultrasound guided central line insertions is becoming the gold standard in neonates, as the entire vascular anatomy is delineated and variations in anatomy clearly identified; hence avoiding multiple attempts and complications.Contrast injected X-rays confirmation even when the catheter is radio-opaque is effective in accurate tip identification and helps in preventing tip related complications.